AMPK: a master energy regulator for gonadal function - Bertoldo, Michael; Faure, Melanie; Dupont, Joëlle; Froment, Pascal (Frontiers in Neuroscience, 2015)
From C. elegans to mammals (including humans), nutrition and energy metabolism significantly influence reproduction. At the cellular level, some detectors of energy status indicate whether energy reserves are abundant (obesity), or poor (diet restriction). One of these detectors is AMPK (5′ AMP-activated protein kinase), a protein kinase activated by ATP deficiency but also by several natural substances such as polyphenols or synthetic molecules like metformin, used in the treatment of insulin resistance. AMPK is expressed in muscle and liver, but also in the ovary and testis. This review focuses on the main effects of AMPK identified in gonadal cells. We describe the role of AMPK in gonadal steroidogenesis, in proliferation and survival of somatic gonadal cells and in the maturation of oocytes or spermatozoa. We discuss also the role of AMPK in germ and somatic cell interactions within the cumulus-oocyte complex and in the blood testis barrier. Finally, the interface in the gonad between AMPK and modification of metabolism is reported and discussion about the role of AMPK on fertility, in regards to the treatment of infertility associated with insulin resistance (male obesity, polycystic ovary syndrome).